Initiation to combat sports from the perspective of ecological dynamics: the Constraints-Led Approach - Sánchez-García, Raúl (Revista de Artes Marciales Asiáticas, 2025)
This pre-eminently theoretical article aims to lay the foundations for an introduction to combat sports based on a motor learning model known as ecological dynamics, which tries to articulate the theories of James Gibson and Nikolai Bernstein with dynamical systems. More specifically, the article criticizes the cognitivism implicit in the notion of “knowing how to fight” (developed from comprehensive approaches) and proposes instead the concepts of combat motor literacy and combat dexterity from the perspective of ecological dynamics. The article also offers a series of pedagogical recommendations for the introduction to combat sports through modified games following the constraints-led approach (CLA). Likewise, it offers a training proposal from MMA and teaching practice using modified games from judo and grappling/Brazilian jiujitsu (BJJ).